Pembelajaran Daring Menggunakan Problem Based untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMPIT Nurul ‘Ilmi Tenggarong - Nurkholis Nurkholis; Sitti Rahma Yunus; Dewi Wahyuni (Universitas Negeri Makassar, 2024)
This research is motivated by the low learning outcomes of class VIII students at SMPIT Nurul 'Ilmi Tenggarong, especially when learning is carried out online due to the Covid-19 pandemic. This study aims to determine the use of the Problem Based Learning model in improving the learning outcomes of class VIII students of SMPIT Nurul 'Ilmi Tenggarong. This research is a classroom action research conducted in 2 cycles. The stages in conducting this research include planning, implementation, observation, and reflection carried out in each cycle. The data collection technique uses written tests in the form of multiple choice questions and observations. Data analysis is carried out by comparing the evaluation scores of each cycle based on the minimum completeness criteria, namely ≥ 70. The subjects of the study were 15 class VIII Halimah students. The results of this study indicate that there has been an increase in student learning outcomes. The improvement is known from the results of student learning evaluations, namely in cycle I, 11 students or 73.3% completed with an average score of 74.67 and in cycle II, 13 students or 86.6% completed with an average score of 82.00. The results of this study can be concluded that online learning using the Problem Based Learning model can improve the learning outcomes of class VIII students of SMPIT Nurul 'Ilmi Tenggarong.